2022
DOI: 10.3389/fmed.2022.857135
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic Profiling in Synovial Tissue

Abstract: The analysis of synovial tissue offers the potential for the comprehensive characterization of cell types involved in arthritis pathogenesis. The studies performed to date in synovial tissue have made it possible to define synovial pathotypes, which relate to disease severity and response to treatment. Lipidomics is the branch of metabolomics that allows the quantification and identification of lipids in different biological samples. Studies in animal models of arthritis and in serum/plasma from patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 135 publications
0
8
0
Order By: Relevance
“…LPL is an important member of the lipase family, which can promote the hydrolysis of TG, cholesterol, and phospholipids and catalyze the decomposition of TG-rich chylous particles into FFAs and glycerol monoesters to help synthesize fatty acids ( Al-Shammari et al, 2022 ). FFA in serum can reflect the lipolytic activity in adipose tissue ( Coras et al, 2022 ). We also found that the addition of B. licheniformis to the diet promotes fatty acid synthesis via enzyme (such as FAS) upregulation, further promoting lipid metabolism in Pekin ducks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LPL is an important member of the lipase family, which can promote the hydrolysis of TG, cholesterol, and phospholipids and catalyze the decomposition of TG-rich chylous particles into FFAs and glycerol monoesters to help synthesize fatty acids ( Al-Shammari et al, 2022 ). FFA in serum can reflect the lipolytic activity in adipose tissue ( Coras et al, 2022 ). We also found that the addition of B. licheniformis to the diet promotes fatty acid synthesis via enzyme (such as FAS) upregulation, further promoting lipid metabolism in Pekin ducks.…”
Section: Discussionmentioning
confidence: 99%
“…Glycerol esters are composed of long-chain acyl groups, alkyl groups, and polar alcohols and can be classified as monoacylglycerol (1 FA), diacylglycerol (2 FA), and triacylglycerol (3 FA) depending on the number of acyl molecules. FAs generally consist of a straight chain of an even number of carbon atoms (also known as an acyl chain) with a hydrogen atom at one end of the chain along the length of the chain and a carboxyl group (-COOH) at the other end ( Coras et al, 2022 ). Serum metabolomic analysis of Pekin ducks fed a B .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, pharmacological inhibition or genetic ablation of acid sphingomyelinase reduced symptoms of arthritis (including joint swelling) and circulating pro-inflammatory cytokines in the arthritic joints of mice [ 87 ]. Animal studies also indicate that the regulation of synovitis is greatly regulated through the S1P pathway [ 88 ]. In collagen-induced arthritis mice, the S1P receptor is upregulated in the synovial tissue and inflammation increases S1P/S1P3 signaling, which stimulates the overproduction of IL-6 in fibroblast-like synoviocytes [ 89 ].…”
Section: Evidence Regarding Ceramides In Patients With Airdsmentioning
confidence: 99%
“…This ceramide-related apoptosis has also been noted in RA through the inhibition of anti-apoptotic kinases, such as the Akt, or the extracellular signal-regulated kinase ½ cascade (ERK1/2) [ 77 ]. Collectively, the data indicate that S1P could be a promising therapeutic target in RA, although more research is deemed necessary [ 88 ].…”
Section: Evidence Regarding Ceramides In Patients With Airdsmentioning
confidence: 99%
“…Glycerol esters are composed of long-chain acyl groups, alkyl groups, and polar alcohols and can be classified as monoacylglycerol (1 FA), diacylglycerol (2 FA), and triacylglycerol (3 FA) depending on the number of acyl molecules. FAs generally consist of a straight chain of an even number of carbon atoms (also known as an acyl chain) with a hydrogen atom at one end of the chain along the length of the chain and a carboxyl group (-COOH) at the other end (Coras et al, 2022). Serum metabolomic analysis of Pekin ducks fed a B. licheniformis-supplemented diet revealed a significantly altered lipid metabolism in these ducks, which was mainly manifested in the regulation of glycerophospholipids, fatty acids, and glycerolipid metabolites, suggesting that B. licheniformis influences the synthesis and catabolism of glycerophospholipids, fatty acids, and glycerolipids to enhance growth performance in Pekin ducks.…”
Section: Discussionmentioning
confidence: 99%